Cosine-/Sine-Modulated Filter Banks General Properties, Fast Algorithms and Integer Approximations - Britanak, Vladimir (Springer International Publishing, 2018)
This book covers various algorithmic developments in the perfect reconstruction cosine/sine-modulated filter banks (TDAC-MDCT/MDST or MLT, MCLT, low delay MDCT, complex exponential/cosine/sine-modulated QMF filter banks), and near-perfect reconstruction QMF banks (pseudo-QMF banks) in detail, including their general mathematical properties, matrix representations, fast algorithms and various methods to integer approximations being recently a new transform technology for lossless audio coding. Each chapter will contain a number of examples and will conclude with problems and exercises. The book reflects the research efforts/activities and achieved results of the authors in the time period over the last 20 years. Details the perfect reconstruction cosine/sine-modulated analysis/synthesis filter banks (unified treatment of TDAC-MDCTs/MDSTs both for the evenly and oddly stacked systems, MLT, ELT, MCLT) and near-perfect cosine/sine-modulated QMF banks Describes the Spectral Band Replication (SBR), a novel enhancement compression technology also known as a bandwidth extension method which significantly improves the compression efficiency of perceptual audio/speech coding schemes Covers various approaches to integer approximations of the MDCT/MDST (Integer MDCT/MDST) leading to their real-time multiply-free implementations for lossless audio coding.